Case Report: Pediatric Chronic Active Epstein-Barr Virus Infection With Giant Sinus of Valsalva Aneurysms and Aorta and Its Branch Dilations - Li, Qirui; Li, Guyu; Shao, Daming; Yarrabolu, Tharak; Yue, Yuan (Frontiers in Pediatrics, 2022)
Chronic active Epstein-Barr virus infection (CAEBV), which often manifests as persistent infectious mononucleosis-like symptoms and can involve multiple organs, is a prolonged or reactivated status of primary EBV infection. Cardiovascular damage is one of the rare but severe complications correlated with poor prognosis among all CAEBV patients. Few published articles have demonstrated systemic arterial lesions involving branches of the aorta as cardiovascular complications. Herein, we report a rare pediatric case of CAEBV associated with giant sinus of Valsalva aneurysms and aorta and its branch dilations.